Meaning and Context in Computer Programs. - VIDELA, ALVARO (Communications of the ACM, 2022)
The article examines the concepts of context and meaning for computer programmers and how programmers can utilize information when coding. The article discuses problem domains and source code changes and words used inside the program and computer security.